Pengaruh Inquiry Terbimbing Terhadap Hasil Belajar Kognitif Peserta Didik Kelas XI MIPA SMA Negeri 1 Sukamulia - Ermila Mahariyanti (Jurnal Ilmiah Wahana Pendidikan, 2020)
This research as aim to know the influence of guidence inquiry toward student cognitive outcome on eleventh grade of SMAN 1 Sukamulia. This study was quasi experimental research in form of pretest and posttest for experimental and control group design. There are two group were chosen randomly pretest and posttest for experimental and control group. The technique of collecting data was used student outcome instrument. Meanwhile data analysis was used T test using SPSS 16.0. Based on data analysis, it can be concluded that the learning model of guidence inquiry has influence towards students’ cognitive outcome on eleventh grade students of SMAN 1 Sukamulia. It can be seen from the significance result of T test is 0.000<0,05.